2011
DOI: 10.1002/chem.201001533
|View full text |Cite
|
Sign up to set email alerts
|

“Click” Immobilization on Alkylated Silicon Substrates: Model for the Study of Surface Bound Antimicrobial Peptides

Abstract: We describe an effective approach for the covalent immobilization of antimicrobial peptides (AMPs) to bioinert substrates via CuI-catalyzed azide–alkyne cycloaddition (CuAAC). The bioinert substrates were prepared by surface hydrosilylation of oligo-(ethylene glycol) (OEG) terminated alkenes on hydrogen-terminated silicon surfaces. To render the OEG monolayers “clickable”, mixed monolayers were prepared using OEG-alkenes with and without a terminal alkyne protected by a trimethylgermanyl (TMG) group. The mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 74 publications
1
45
0
Order By: Relevance
“…In contrast, immobilized peptide on a planar solid surface may collectively act on the bacteria with only other neighboring, localized peptide molecules. Another reason may relate to peptide density, 1.5–2× greater for the beads than the planar surface, which is in concurrence with previous studies demonstrating a relationship between peptide densities and activity . Although less potent, the ability to derive efficacy in the planar glass immobilized systems indicates the substrate shape/size does not appear to play a significant role other than limiting potency.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, immobilized peptide on a planar solid surface may collectively act on the bacteria with only other neighboring, localized peptide molecules. Another reason may relate to peptide density, 1.5–2× greater for the beads than the planar surface, which is in concurrence with previous studies demonstrating a relationship between peptide densities and activity . Although less potent, the ability to derive efficacy in the planar glass immobilized systems indicates the substrate shape/size does not appear to play a significant role other than limiting potency.…”
Section: Discussionsupporting
confidence: 86%
“…The reduction was attributed to tethering parameters such as peptide density, peptide accessibility and spacer length as well as adverse influence on parameters that are critical for lytic behavior such as diffusivity, flexibility and membrane permeation. Moreover, Li et al suggests a relationship between peptide densities and activity, while also identifying surface distribution, particularly effective local concentrations, as important for efficacy . The concentration and density of immobilized SMAP_c and c_SMAP on the superparamagnetic beads were variable to a certain degree and likely influenced the degree of potency compared with the soluble forms.…”
Section: Discussionmentioning
confidence: 99%
“…Quadrisected corneas were incubated overnight at 48C on ice in Hank's balanced salt solution (Gibco) containing dispase (25 caseinolytic U/mL; Becton Dickinson) and 5 lg/mL gentamicin (A.G. Scientific, Inc., San Diego, CA). 20 Corneal epithelial cells were then detached from the stroma by gently scraping the corneal surface with a scalpel. The removed cells were digested for 5 minutes in 0.25% trypsin-EDTA (Gibco) at 378C followed by the addition of an equal volume of heat inactivated fetal bovine serum (FBS; Gibco) and were centrifuged at 450g for 5 minutes.…”
Section: Methods Antibodiesmentioning
confidence: 99%
“…13 We have previously shown that the fluorously immobilized films were stable against desorption during the subsequent covalent modification in aquous solutions. 27, 28 The alkynyl surface A allows site-specific attachment of the peptide with an OEG-azido tag ( N 3 -EG 12 -IG-25 ) via click reaction to provide the surface B . Random grafting of the unmodified peptide IG-25 onto the carboxylic acid surfaces C was performed using a procedure similar to a reported one.…”
Section: Resultsmentioning
confidence: 99%